Evaluation of Biophysical Interaction between Newly Synthesized Pyrazoline Pyridazine Derivative and Bovine Serum Albumin by Spectroscopic and Molecular Docking Studies - Abdulrahman A. Al-Mehizia; Ahmed H. Bakheit; Seema Zargar; Mashooq A. Bhat; Majid Mohammed Asmari; Tanveer A. Wani (Journal of Spectroscopy)
In this research, the pyrazoline pyridazine derivative 7-methyl-2-phenyl-4-(3,4,5-trimethoxyphenyl)-2H-pyrazolo[3,4-d]pyridazine (5d) was studied for its interaction with bovine serum albumin (BSA). Various spectroscopic techniques along with molecular docking analysis were utilized to understand the mechanism of interaction. The quenching of BSA fluorescence by using investigational drug 5d was the basic principle for the methodology. Spectrofluorometric methods and UV-absorption studies were conducted for exploration of the 5d and BSA binding mechanism. The fluorescence quenching mechanism involved in BSA and 5d interaction was static quenching, and a complex formation also occurred between them. Both enthalpy and entropy attained positive values suggesting involvement of hydrophobic forces in BSA and 5d interaction. The Förster distance of 2.23 nm was calculated by fluorescence resonance energy transfer (FRET). An alteration in BSA secondary structure was proven from the conformational studies of BSA-5d interaction. This binding interaction study provided a basis to comprehend the binding interaction between 5d and BSA. These results provided information about sites of BSA involved in its interaction with 5d.